2020
DOI: 10.1590/0103-8478cr20200337
|View full text |Cite
|
Sign up to set email alerts
|

Milk quality in small farms from Southern Region of Brazil

Abstract: This study aimed to evaluates some physical chemical aspects of chilled raw milk that meet Brazilian quality standards in smallholder farms from southern Region of Brazil. The fat content, crude protein (CP), total solids (TS), somatic cell count (SCC), and total plate count (TPC) of the chilled raw milk from 78 smallholder farms was analyzed between Oct 2014 and Feb 2017. It was found that 96% of the samples met the Brazilian regulations for fat content, 87% for CP, and 91% for TS. The mean values of TPC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…For milk constituents, the highest percentages of non-compliance with the minimum requirements for current legislation were 14.2% for fat and 8.5% for total solids (Table 3). On the other hand, Candiotto et al (2020) in bovine milk farms in the southern region, they verified only 4% of non-compliance of the farms in relation to the current legislation for fat, however, close to the results obtained for total solids (9%).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…For milk constituents, the highest percentages of non-compliance with the minimum requirements for current legislation were 14.2% for fat and 8.5% for total solids (Table 3). On the other hand, Candiotto et al (2020) in bovine milk farms in the southern region, they verified only 4% of non-compliance of the farms in relation to the current legislation for fat, however, close to the results obtained for total solids (9%).…”
Section: Resultssupporting
confidence: 72%
“…In a study conducted by Candiotto et al (2020) in small properties in the southern region of Brazil, the authors found that 56.1% and 56.8% of the samples taken from October 2014 to July 2016 did not meet the Brazilian regulations for SCC and SPC, respectively. Esses resultados se aproximam dos resultados encontrados no presente trabalho para a SPC (53%).…”
Section: Resultsmentioning
confidence: 99%
“…We measured five different characteristics of technification in dairy production (Table 1), following the milk production systems prevalent in Brazil [39]: (i) productivity [40], measured by daily milk production; (ii) feed management [41,42], measured by primary forage diet, fertilizer pasture management, time of supplementary feed, criterium to supplement, and addition of vitamins to supplement; (iii) milking management [43], measured by milking method, milking frequency, and farm infrastructure for milking; (iv) sanitary control [44], measured by cleaning of udder before milking and CMT test (California Mastitis Test); (v) genetics and breeding [45], measured by breeding program for productivity improvement, selective breeding method and pregnancy diagnosis. We used daily milk production as a measure of productivity because farmers had no information on milk production per cow.…”
Section: Technification Variables and Farm Characteristicsmentioning
confidence: 99%